Poems for a Small Park - E.D. Blodgett (Mingling Voices, 2008)
Blodgett wrote his poems for a small park in English and some in French, but was able to have some of them translated into Cree, Michif, Chinese, and Ukrainian. This reflects Edmonton's unique multicultural ambience and the roles of diverse cultures in the making of the city. The powerful images and thoughtful metaphors in these short lyrics show readers the connections between Canadian nature (even within city limits) and the sublime, especially in the overwhelming silence we can sense outdoors - if we pay attention. The poet speaks to change by helping us see natural phenomena around us in a different light each time we read his poems